Sociodemographic Factors Associated with Nutritional Status and Ultra-Processed Food Consumption among Adolescent - Farah Kurnia Mariestu; Budiyanti Wiboworini; Veronika Ika Budiastuti (Future Science, 2024)
Surakarta has the highest frequency of overweight and obesity in adolescents (11,47%) based on Central Java Basic Health Research 2018. Several factors, such as sociodemographics and dietary habits, might have an impact on nutritional status. Meanwhile, sociodemographic conditions can also influence ultra-processed food consumption habits. The purpose of this study was to evaluate the correlation between sociodemographic, nutritional status, and frequency of ultra-processed food consumption among adolescents. The research was carried out at five senior high schools in Surakarta City, Indonesia, in five different sub-districts. As many as 114 students were taken using proportionate random sampling. Data on sociodemographic conditions were obtained from filling out questionnaires. Weight and height are used to calculate body mass index according to age. The Food Frequency Questionnaire was used to collect information about the frequency of ultra-processed food consumption. The correlation of sociodemographics with nutritional status and frequency of ultra-processed food consumption was analyzed using Chi-Square. The result showed that the prevalence of overweight or obesity and non-overweight and obesity is 18.4% and 81.6% respectively. Most of the respondents often consume ultra-processed food (51.8%). There was a correlation between gender and occupational of the mother with nutritional status (p 0.034 and 0.024) and gender correlated with ultra-processed food consumption (p 0.043). There was a correlation between ultra-processed food with nutritional status (p 0.003). The conclusion is gender and occupation of the mother correlate with nutritional status. Gender correlates with the frequency of ultra-processed food consumption. Meanwhile, the frequency of ultra-processed food consumption correlates with nutritional status. Parents need to be aware of their kid's food choices.